OPTIMALISASI PENCEGAHAN DINI STUNTING DAN PENINGKATAN KAPASITAS SDM DALAM PEMAHAMAN PSIKOLOGI TUMBUH KEMBANG ANAK - Ahmadi, Mirzam Arqy; Fachrunisa, Rahma Ayuningtyas; Chairunnisa, Bella Ananda; Kurniawan, Fidaus; Esaputra, Ahmad Baihaqi; Shobahiya, Mahasri; Pambudi, Haning Lestari Dwi (INTEGRITAS : Jurnal Pengabdian, 2024)
Stunting is a serious health issue in Indonesia caused by chronic malnutrition, negatively impacting both physical growth and psychological development in children. Although the prevalence of stunting in Indonesia decreased from 37.2% in 2013 to 30.8% in 2018, it remains far from the 14% reduction target set for 2024. This study evaluates the effectiveness of a community service program in Joyosuran Village aimed at reducing stunting rates and improving children's psychological well-being through education and group discussions. The methods used included workshops and focus group discussions (FGD) with 50 participants from the Aisyiyah organization. The results indicate an increased understanding among participants regarding stunting prevention and child psychology management, and the application of this knowledge in daily life. The program successfully educated the community about the importance of nutritious diets and emotional support for children, demonstrating that a comprehensive approach can contribute to reducing stunting and improving children's psychological health..